THE INFLUENCE OF THE INTAKE MANIFOLD SYSTEM CONCERNING THE PERFORMANCES OF THE INTERNAL COMBUSTION ENGINE - Ioan HITICAS; Danila IORGA; Liviu MIHON; Narcis URICANU; George PICIOREA (Fiabilitate şi Durabilitate, 2012)
—Comfort and safety, this are two targets for today designer and engineering of the road vehicle. Increasing the performances of the engine through all the system of the thermal engine, have concerned the main vehicles companies to develop all the systems of the engine. One of this system is and the air intake system. This paper presents parts of the mathematic calculation and the experimental tests of the intake manifold system concerning the performances of the engine. The vehicle used was a BMW vehicle. We study the air flow inside the filter housing with CFD (Computational Fluid Dynamics) simulation, being mentioned the high importance of this system on increasing the performances of the engine